An Image Steganography Scheme using Randomized Algorithm and Context-Free Grammar - Bassil, Youssef (Journal of Advanced Computer Science & Technology, 2012)
Currently, cryptography is in wide use as it is being exploited in various domains from data confidentiality to data integrity and message authentication. Basically, cryptography shuffles data so that they become unreadable by unauthorized parties. However, clearly visible encrypted messages, no matter how unbreakable, will arouse suspicions. A better approach would be to hide the very existence of the message using steganography. Fundamentally, steganography conceals secret data into innocent-looking mediums called carriers which can then travel from the sender to the receiver safe and unnoticed. This paper proposes a novel steganography scheme for hiding digital data into uncompressed image files using a randomized algorithm and a context-free grammar. Besides, the proposed scheme uses two mediums to deliver the secret data: a carrier image into which the secret data are hidden into random pixels, and a well-structured English text that encodes the location of the random carrier pixels. The English text is generated at runtime using a context-free grammar coupled with a lexicon of English words. The proposed scheme is stealthy, and hard to be noticed, detected, and recovered. Experiments conducted showed how the covering and the uncovering processes of the proposed scheme work. As future work, a semantic analyzer is to be developed so as to make the English text medium semantically correct, and consequently safer to be transmitted without drawing any attention.